Smaller Feedback-Related Negativity (FRN) Reflects the Risky Decision-Making Deficits of Methamphetamine Dependent Individuals - Na Zhong; Tianzhen Chen; Youwei Zhu; Hang Su; Xiaolu Ruan; Xiaotong Li; Haoye Tan; Haifeng Jiang; Jiang Du; Min Zhao; Min Zhao (Frontiers in Psychiatry, 2020)
Methamphetamine (MA) chronic users show risky decision-making deficits. However, the neural mechanisms underlying these deficits remain unclear. A case-control study was conducted to understand how MA users and healthy controls differ in electrophysiological responses associated with series decision-making. Electroencephalography of 31 MA users and 27 healthy controls was recorded when they performed the Balloon Analogue Risk Task involving risky decision-making with uncertain gain or loss. Feedback-related negativity (FRN) was measured and their association with their risky decision-making and impulsivity were examined. Compared to healthy controls, MA users showed smaller peak FRN amplitudes in fronto-central electrodes (F (1,56) =4.559, p=0.037), and the attenuated peak FRN amplitudes correlated with more risk-taking behavior (r=0.48, p=0.012). Besides, MA users exhibited later FRN (F (1,56) = 7.561, p=0.008) and earlier P300 (F (1,56) = 3.582, p = 0.041) compared to healthy controls in fronto-central electrodes, which were correlated with higher score of impulsivity. These findings provided further evidence that MA users showed insensitivity to negative feedback in risky decision-making. FRN might be a promising biomarker of dependence.